Facile Synthesis and Characterization of gCN, gCN-Zn and gCN-Fe Binary Nanocomposite and Its Application as Photocatalyst for Methylene Blue Degradation - Hasan Eskalen; Mustafa Kavgacı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The combustion method to obtain for pure graphitic carbon nitride (gCN) and two binary nanocomposites, gCN-Zn - gCN-Fe have been used in the present study. The structural, morphological, thermal and optical characterizations of the syhtesized samples were characterized with X-ray diffraction, scanning electron microscopy, thermogravimetric analysis (TGA) and UV-Vis spectroscopy. The intensity of characteristic gCN peak at (002) crystalline plane decrease with formation of binary nanocomposites was observed. The EDX spectra supports presents of Zn and Fe element in binary nanocomposites. The bandgap of pristine gCN is calculated as 2.75 eV and it decreases to 2.58 eV and 2.50 eV for Zn and Fe addition. The degradation capacity of pristine gCN and synthesized binary nanocomposites showed an enhanced photodegradation performance for binary composite relative to pristine gCN was observed. The maximum degradation performance was observed at gCN-Zn binary composite. The obtained composites with this simple synthesis method and cost effective raw materials used for the photodegradation of methylene blue dye detail.